IMPLEMENTATION OF WASTE MANAGEMENT POLICY IN BUMI BERINGIN VILLAGE, WENANG DISTRICT, MANADO CITY - Regina Sondakh; Evie E. Masengi; Joyce Ch. Kumaat (PT. Radja Intercontinental Publishing, 2026)
This study aims to determine, analyze, and describe the waste transportation system and the factors that influence the implementation of policies on waste management by reviewing several indicators, namely household waste sorting, waste transportation to the SPA (Intermediate Transition Station) by garbage motorbikes, then continued to the TPA (Final Disposal Site) by garbage trucks, and also the timeliness of waste transportation. The research method used is a descriptive method with a qualitative approach using primary and secondary data obtained through interviews, observations, and documentation. The results of this study indicate that good waste management can support the optimization of the waste transportation process. The implementation of waste management policies on the transportation system still encounters various obstacles, such as a lack of public awareness in sorting waste, a lack of transportation fleets, delays in transportation, and a lack of maximum supervision. These obstacles cause the waste transportation system to not run optimally. In addition, the implementation of policies in waste management greatly affects the smoothness and optimization of the waste transportation system, so there is a need for improved facilities and infrastructure, community participation, and more intensive supervision so that the waste transportation system can run well, more effectively, efficiently, and sustainably.